Application Value of Information-Based Health Education and Continuity of Care in Patients With Peptic Ulcer - Liu, Aihong; Kuang, Yuhua; Huang, Ruiping; Ge, Qunying (Frontiers in Public Health, 2021)
Objective: This study is to assess the application value of information-based health education and continuity of care in PU (peptic ulcer) patients. Methods: 116 patients with PU who have been treated in our hospital between January 2019 and October 2020 were taken as research object and equally assigned to a control group and an observation group in a random manner. In contrast to the routine care applied to the control group, the observation group received information-based health education and continuity of care intervention. The clinical efficacy, the mastery of health knowledge, self-care ability, medication compliance, quality of life, mental state and nursing satisfaction of the two groups were compared. Results: After the intervention, the total effective rate, health knowledge adequate rate, ESCA (Exercise of Self-Care Agency) scores of all dimensions, SF-36 (the MOS item short from health survey, SF-36) scores of all dimensions, medication compliance rate and total nursing satisfaction of the observation group all notably exceeded those of the control group, with a P value less than 0.05. Patients of the group with continuity of care intervention showed lower SAS (Self-Rating Anxiety Scale) and SDS (Self-Rating Depression Scale) scores, as compared to the group with conventional care (P<0.05). Conclusion: Information-based health education and continuity of care elevates the clinical efficacy, medication adherence and nursing satisfaction of PU patients, enhances disease-related knowledge of patients and their self-care ability, and eventually ameliorates the quality of life and psychological state. It is worthy of clinical application.